Correlation of QRS duration with intraventricular mechanical dyssynchrony on tissue Doppler imaging in heart failure (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Wide QRS complex with left bundle branch block morphology is one of the three criteria for cardiac resynchronization therapy (CRT) in heart failure (HF) patients who do not improve on medical management. Approximately 30% of patients do not respond to CRT. This study investigates to find out to what extent the wide QRS duration correlates with the intraventricular mechanical dyssynchrony (IVMD) as measured by Tissue Doppler Imaging (TDI) echocardiography.Methods: The HF patients of dilated or ischemic cardiomyopathy with ejection fraction £35% admitted in the medical ward of Patan Hospital, Nepal from March to August 2017 were enrolled in the study. They were divided into two groups, narrow QRS duration of